Development of Surface-Modified Microelectrode Arrays for the Electrochemical Detection of Dihydrogen Phosphate - Berduque, A.; Herzog, G.; Watson, Y.; Arrigan, Damien; Moutet, J.; Reynes, O.; Royal, G.; Saint-Aman, E. (Wiley - VCH Verlag GmbH & Co. KGaA, 2005)
Platinum and gold microelectrode arrays (MEAs), fabricated on silicon substrates with different geometric characteristics, were surface-modified by the potentiostatic electropolymerization of the pyrrole-ferrocene derivative Py(CH2)3NHCOFc, in the case of the platinum MEAs, and chemisorption of the thiol-functionalized ferrocene HS(CH2)6Nþ(CH3)2Fc, in the case of the gold MEAs. Cyclic voltammetry of these MEAs was typical of thin film behavior. The modified MEAs were investigated for the detection of the dihydrogen phosphate mono-anion in nonaqueous media via differential pulse voltammetry. This was based on electrostatic interaction and/or hydrogenbonding between the target anion and the amide-ferrocene or ammonium-ferrocene functionalized electrode surfaces. A decrease in the ferrocene (Fc) oxidation peak current with a concomitant increase in the peak current of a new peak at lower potentials was observed when the concentration of the dihydrogen phosphate was increased.